PEMBERDAYAAN PETERNAK KERBAU DI KECAMATAN MARONGE KABUPATEN SUMBAWA - Eko Budi Santoso; Keke Sulalatin Fathiah (Jurnal Ilmiah Wahana Bhakti Praja, 2017)
Sumbawa Regency has the potential of superior livestock in the form of local buffalo Sumbawa which has a large enough posture and has the potential to become a center of national buffalo cattle that can be a main source of national animal protein. But in reality in the field, buffalo breeders in Sumbawa regency is a society that has not been empowered, indicated by the low income of the farmer. While one of the duties of local government is to do empowerment for the people who are less empowered, therefore it is important to examine how the implementation of empowerment has been done by the Government of Sumbawa Regency to buffalo breeders in Sumbawa regency, especially in Maronge subdistrict as one of the districts that have been established UPTD specifically to handle the affairs of buffalo cattle and the only district that has center of buffalo cattle breeding in Sumbawa Regency. The purpose of this study is to describe the empowerment of Sumbawa buffalo breeders that have been done by the Government of Sumbawa Regency, especially in Maronge District, Sumbawa Regency.The research method used was descriptive qualitative research, with the operationalization of the concept of empowerment used is adopted from Mardikanto's view (2015) which states that empowerment scope is at least 4 dimension, those are human development, bussiness development, environment development, and Institutional Development. Data collection techniques used are interview techniques, observation and documentation. In the interview technique, the selection of informant sample with purposive sampling technique. His analytical technique uses narrative descriptive analysis techniques and triangulation of sources as well as triangulation of data collection methods. The results show that empowerment has been implemented but not yet optimal because there are still some weaknesses, such as: 1) less intensive in knowledge, skill, and attitude building and still need a continuous ecompaniment; 2) lack of access to information and technology; 3) lack of construction of other supporting infrastructure due to budget constraints; and 4) weak institutional and partnership networks in micro farmers and lack of farmer initiatives due to stimulation of government programs. It is recommended to Sumbawa Regency Government to: 1) increase training frequency and in specific form; 2) improved access to information and technology; 3) budget allocation for construction of supporting infrastructure and maintenance of buildings; as well as raising awareness and initiative of breeders for institutional improvement and self-reliance. atau dalam Bahasa IndonesiaKabupaten Sumbawa memiliki potensi ternak unggul berupa kerbau lokal Sumbawa yang memiliki postur yang cukup besar dan memiliki potensi untuk menjadi sentra ternak kerbau nasional yang dapat menjadi sumber protein hewani nasional. Namun kenyataannya di lapangan, peternak kerbau di Kabupaten Sumbawa merupakan masyarakat yang belum berdaya, ditunjukkan oleh masih kecilnya rata-rata pendapatan peternak tersebut. Sementara salah satu tugas Pemerintah daerah adalah untuk melakukan pemberdayaan bagi masyarakatnya yang kurang berdaya. Oleh karena itu penting untuk diteliti mengenai bagaimana  pelaksanaan pemberdayaan yang telah dilakukan oleh Pemerintah Kabupaten Sumbawa terhadap peternak kerbau di Kabupaten Sumbawa, khususnya di Kecamatan Maronge sebagai salah satu kecamatan yang telah dibentuk UPTD khusus untuk menangani urusan terkait ternak kerbau dan satu-satunya kecamatan yang memiliki pusat pembibitan ternak kerbau di Kabupaten Sumbawa. Tujuan penelitian ini adalah untuk menggambarkan tentang pemberdayaan kepada peternak kerbau Sumbawa yang telah dilakukan oleh Pemerintah Kabupaten  Sumbawa, khususnya di Kecamatan Maronge Kabupaten Sumbawa. Metode penelitian yang dilakukan adalah penelitian kualitatif deskriptif, dengan operasionalisasi konsep pemberdayaan yang digunakan diadopsi dari pandangan Mardikanto (2015) yang menyatakan bahwa lingkup pemberdayaan itu paling tidak mencakup 4 dimensi yaitu Bina manusia, Bina Usaha, Bina Lingkungan, dan Bina Kelembagaan. Teknik pengumpulan data yang digunakan adalah teknik wawancara, observasi dan dokumentasi. Pada teknik wawancara, dilakukan pemilihan sampel informan dengan teknik purpossive sampling. Teknik analisismya menggunakan teknik analisis deskriptif naratif dan triangulasi sumber maupun triangulasi metode pengumpulan data. Hasil penelitian menunjukkan bahwa pemberdayaan telah dilaksanakan namun belum optimal karena masih terdapat beberapa kelemahan, seperti: 1) pembinaan pengetahuan, ketrampilan dan sikap kurang intensif dan masih perlu pendampingan yang kontinyu; 2) kurangnya akses informasi dan teknologi; 3) kurangnya pembangunan prasarana pendukung lainnya karena keterbatasan anggaran; dan 4) lemahnya kelembagaan dan jejaring kemitraan pada peternak mikro dan kurangnya inisiatif peternak akibat stimulasi program pemerintah. Direkomendasikan kepada Pemkab Sumbawa untuk: 1) meningkatkan frekuensi pelatihan dan dalam bentuk yang spesifik; 2) peningkatan akses informasi dan teknologi; 3) pengalokasian anggaran untuk pembangunan prasarana penunjang dan pemeliharaan bangunan; serta peningkatan kesadaran dan inisitaif peternak untuk peningkatan kelembagaan dan kemandirian